Lower–Middle Ordovician brachiopods from the Eastern Cordillera of Peru: evidence of active faunal dispersal across Rheic and Iapetus oceans - Colmenar Lallena, Jorge (2024)
[ENG] New Floian and early middle Darriwilian brachiopod assemblages of the San José Formation of the Eastern Cordillera of Peru are presented. A new genus and species, Apurimella santiagoi, and two new species, Phragmorthis henrylunae and Nocturnellia ashaninka, are described. The assemblages also contain additional characteristic taxa demonstrating links with other proto-Andean localities (Peruvian Altiplano, Argentinian Eastern Cordillera, Famatina) as well as with some localities of Baltica (Estonia, Ingria, Norway), Ganderia (Anglesey, Tramore, Indian Bay, Summerford, Miramichi), peri-Laurentia (Mayo, Svalbard) and Laurentia (Klamath Mountains). Those shared genera indicate dynamic faunal exchanges between the Peruvian Eastern Cordillera and these terranes during the Early–Middle Ordovician transition, suggesting active brachiopod dispersal mechanisms across the Rheic and Iapetus oceans. These connections seem to have still been active by the middle Darriwilian, as suggested by the presence of Phragmorthis in the Darriwilian assemblages of Cuyania and Laurentia. Similarly, the new Peruvian Nocturnellia species is of particular interest, given that this genus is likely to have originated in South China during the Floian, but extended its distribution to Avalonia and to high-latitude peri-Gondwana by the Dapingian. It thrived there until the middle Darriwilian, but by that time had also reached the proto-Andean margin either via Avalonia across the Rheic Ocean or along the Gondwanan coast from high-latitude settings. All of these occurrences improve our knowledge of Early–Middle Ordovician brachiopod faunas of the northern Central Andean Basin and their relationships with contemporaneous faunas worldwide.